2004
DOI: 10.5194/angeo-22-3843-2004
|View full text |Cite
|
Sign up to set email alerts
|

Wind and turbulence measurements by the Middle and Upper Atmosphere Radar (MUR): comparison of techniques

Abstract: Abstract. The structure-function-based method (referred to as UCAR-STARS), a technique for estimating mean horizontal winds, variances of three turbulent velocity components and horizontal momentum flux was applied to the Middle and Upper atmosphere Radar (MUR) operating in spaced antenna (SA) profiling mode. The method is discussed and compared with the Holloway and Doviak (HAD) correlationfunction-based technique. Mean horizontal winds are estimated with the STARS and HAD techniques; the Doppler Beam Swingin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…Apart from supporting radar imaging, the new multichannel digital receiver system makes it possible to utilize multiple signal‐processing algorithms on the same raw data. Thus, for example, SA‐configuration wind measurements using correlation‐function or structure‐function approaches [ Praskovsky et al , 2004] could be implemented and the information combined with radar imaging information about layer morphology. The potential for such combination of signal‐processing techniques makes the new MUR imaging system a valuable addition to the atmospheric science community.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from supporting radar imaging, the new multichannel digital receiver system makes it possible to utilize multiple signal‐processing algorithms on the same raw data. Thus, for example, SA‐configuration wind measurements using correlation‐function or structure‐function approaches [ Praskovsky et al , 2004] could be implemented and the information combined with radar imaging information about layer morphology. The potential for such combination of signal‐processing techniques makes the new MUR imaging system a valuable addition to the atmospheric science community.…”
Section: Discussionmentioning
confidence: 99%
“…The pattern life time provides the means for estimating turbulent velocities (Holdsworth et al., 2001). This has an advantage that the effects of beam broadening are negligible and thus no beam broadening‐correction is required (Holdsworth et al., 2001; Praskovsky et al., 2004; Rao & Kirkwood, 2005). Since auto‐correlation function is analogous to Doppler‐spectrum, the turbulent velocity is equal to spectral width (in ms −1 ) estimated with the DBS technique.…”
Section: Methodsmentioning
confidence: 99%
“…(1996) for obtaining horizontal winds by developing formulation relating advecting scattering medium to cross correlation/spectrum of echoes in spaced receivers. Different variants of the SA technique have been emerged over the years, like Cross/Auto Correlation Ratio (Holloway et al., 1997), lag of intersection of auto‐ and cross‐correlations (Cohn et al., 1997), slope at zero lag (Lataitis et al., 1995), Cross‐Correlation Ratio (Zhang et al., 2003) and structure‐function‐based analysis (Praskovsky et al., 2004). Several studies have shown that the performance of these different variants is similar to that of FCA (Chau & Balsley, 1998; Doviak et al., 2004; Kumar et al., 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation